Obesity in adolescents with celiac disease: two adolescents and two different presentations - Balamtekin, Necati; Demir, Hülya; Baysoy, Gökhan; Uslu, Nuray; Yüce, Aysel (The Turkish Journal of Pediatrics, 2011)
Celiac disease (CD) usually presents with diarrhea and growth retardation in childhood. Obesity is one of the paradoxical conditions in children with CD. We present two adolescents with CD and obesity. One of these patients was diagnosed as CD with malnutrition. His body weight had returned to normal after a gluten-free diet, and after stopping the diet, he had become obese. The second patient was an obese adolescent presenting with dyspeptic symptoms who was diagnosed as CD. Although rare, pediatricians should remember that obesity might be seen in CD before or after the diagnosis.